Social support as a protective factor for depression among women caring for children in HIV-endemic South Africa. - Casale, M; Wild, L; Cluver, L; Kuo, C (Springer, 2015)
Social support has been shown to be a protective resource for mental health among chronically ill adults and caregiver populations. However, to date no known studies have quantitatively explored the relationship between social support and depression among women caring for children in HIV-endemic Southern Africa, although they represent a high risk population for mental health conditions. Using data from a household survey with 2,199 adult female caregivers of children, living in two resource-deprived high HIV-prevalence South African communities, we conducted hierarchical logistic regression analysis with interaction terms to assess whether social support had a main effect or stress-buffering effect on depression. Findings provide evidence of stress-buffering of non-HIV-related chronic illness, but not HIV-related illness. Results reinforce the importance of social support for the mental health of chronically ill caregivers, and suggest that factors related to the specific nature of HIV/AIDS may be hindering the potential stress-buffering effects of social support among people living with the disease. Implications for future research and interventions are discussed.